Regime hídrico e térmico de neossolos do Semiárido paraibano - Silva, Safira Yara Azevedo Medeiros da (2018)
Soil environmental functions and ecosystems services are related with water availability. In arid and semiarid environments this availability goes thought periods of high and low abundance. Shorts periods of high water availability are caused by rainfall events which supplies water needs. In a toposequence, topography and landform variation determine soil morphology, physics, and chemical biology differences in which soils are developed. Considering the same conditions of soil formation (climatic, biotic, time and parent material) for all soils in the toposequence, the variation in water and heat flux are determined only by topography and landform. Thus, the objective of this study was to evaluate the water content and soil temperature variations in a toposequence with a pedological system composed of a Lithic Torriorthents, Typic Torriorthents and Typic Torripsmamments in the semiarid region of the State of Paraíba, Brazil. For this, morphological (structure, transition, and depth of horizons) and physical (water retention curves and hydraulic conductivity curves) and chemical analyzes (routine for soil classification, organic carbon, and organic matter) were performed. To determine the soil water and thermal regime, the tension and water content and temperature were evaluated with MPS-2 sensors (Decagon Devices®) and monthly samples collected in all soil horizons for one year. The soils present water retained at tensions > 1500 kPa and temperatures > 20ºC for more than 90 days within the control section, which classifies the soil moisture regime as aridic and thermal as hyperthermic according to Soil Survey Division Staff. The Lithic Torriorthents that occur in the shoulder of the toposequence presented the highest water content and lower tension in the driest month (November 2017), which can be attributed to the higher content of organic matter and composition than that of the Typic Torriorthents and Typic Torripsmamments. The soil moisture and temperature regime of these soils is related to the ecosystem services related to the water cycle.